The Employment Standards Enforcement Gap and the Overtime Pay Exemption in Ontario - Thomas, Mark P.; Vosko, Leah F.; Tucker, Eric; Steedman, Mercedes; Noack, Andrea M.; Grundy, John; Gellatly, Mary; Leinveer, Lisa (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2019)
Employment Standards (es) legislation sets minimum terms and conditions of employment in areas such as wages, working time, vacations and leaves, and termination and severance. es legislation is designed to provide minimum workplace protections, particularly for those with little bargaining power in the labour market. In practice, however, es legislation includes ways in which legislated standards may be avoided, including through exemptions that exclude specified employee groups, fully or partially, from legislative coverage. With a focus on the Ontario Employment Standards Act, this article develops a case study of exemptions to the overtime pay provision of the act and regulations and examines in closer detail three specific areas in which exemptions apply. Through this study of the overtime pay exemption, the system of exemptions is presented as a contradictory approach to the regulation of es that, in effect, reduces es coverage, contributes to the avoidance of key legislated standards, and undermines the goal of providing protection for workers in precarious jobs.